The importance of freedom of expression in a democratic state. : Some reflections on the 25th anniversary of the 1997 Constitution of the Republic of Poland - Biłgorajski, Artur (Scientific Journal of Bielsko-Biala School of Finance and Law, 2022)
This study is devoted to the analysis of the role that freedom of expression plays in a democratic state. At the beginning, the author puts forward the theses that: 1) freedom of expression can emerge and function only in democratic countries; 2) without freedom of expression, there can be no democracy; 3) freedom of expression is a value that forms other freedoms and rights; 4) freedom of expression is a guarantee of protection of other freedoms and rights; 5) freedom of expression is a condition for the realisation of political pluralism; 6) freedom of expression is a condition for the realisation of the principle of national sovereignty. The following part of this study is devoted to the verification of the above-mentioned theses.